2020
DOI: 10.1371/journal.pone.0238856
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced p53 interferes with mitophagy in cardiac fibroblasts

Abstract: Anthracyclines are the critical component in a majority of pediatric chemotherapy regimens due to their broad anticancer efficacy. Unfortunately, the vast majority of long-term childhood cancer survivors will develop a chronic health condition caused by their successful treatments and severe cardiac disease is a common life-threatening outcome that is unequivocally linked to previous anthracycline exposure. The intricacies of how anthracyclines such as doxorubicin, damage the heart and initiate a disease proce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…Chemotherapy drugs also contribute to cardiomyocyte dysfunction and death by affecting mitochondrial function. For example, doxorubicin-induced upregulation of p53 inhibits protective mechanisms in cardiac fibroblast mitochondria [ 20 ], and administration of mitochondria-associated protein LRPPRC protects against doxorubicin-induced cardiac injury by inhibiting ROS production [ 60 ]. Anthracycline-mediated cardiotoxicity is also associated with dysregulation of mitochondrial metabolism, although the detailed molecular mechanisms involved are not fully understood [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy drugs also contribute to cardiomyocyte dysfunction and death by affecting mitochondrial function. For example, doxorubicin-induced upregulation of p53 inhibits protective mechanisms in cardiac fibroblast mitochondria [ 20 ], and administration of mitochondria-associated protein LRPPRC protects against doxorubicin-induced cardiac injury by inhibiting ROS production [ 60 ]. Anthracycline-mediated cardiotoxicity is also associated with dysregulation of mitochondrial metabolism, although the detailed molecular mechanisms involved are not fully understood [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that targeted cancer therapies, such as doxorubicin [ 15 ], anthracycline [ 16 ], and cantharidin [ 17 ], can result in cardiovascular toxicities. The adverse effects of chemotherapy drugs may result from impaired mitochondrial function, increased oxidative stress [ 15 , 18 ], increased mitochondria-proteasome interactions [ 19 ], impaired mitochondrial autophagy [ 20 , 21 ], activation of mitochondrial inflammation signaling pathways such as NF- κ B [ 22 ], mitochondrial energy metabolic dysfunction [ 23 ], and mitochondrial apoptosis [ 24 ]. In addition, ER-mediated abnormalities in intracellular calcium signaling, protein misfolding as a result of ER stress, and ER-dependent cell apoptosis [ 25 27 ] can also contribute to cardiomyocyte damage during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of PINK1/Parkin-mediated mitophagy in DOX-induced cardiomyopathy is still in dispute. Some studies claimed that enhanced mitophagy could protect against DOX cardiotoxicity (Mancilla et al, 2020;Xiao et al, 2020), while others stood on the opposite (Gharanei et al, 2013;Catanzaro et al, 2019). These mixed results might be explained by the different model used, different DOX concentrations, different time of treatment, and different degree of cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…DOX can also dysregulate the cytosolic and mitochondrial signaling axes, which leads to mitophagy destruction and arrhythmias, causing impaired mitochondrial clearance, the accumulation of dysfunctional mitochondria, ROS overload, and a lack of Adenosine triphosphate (ATP). Meanwhile, DOX can also phosphorylate BNIP3 and then inhibit mitophagy, which is closely related to the mitochondrial sirtuins (SIRT3-SIRT4) pathway ( 26 , 27 , 150 , 206 , 207 , 221 , 225 , 227 , 228 ). Recently, it was reported that excessive DOX can also significantly induce elevated insulin-like growth factor-II receptor (IGF-IIR) expression, IGF-IIR induces myocardial hypertrophy and cardiomyocyte death in a paracrine/autocrine manner.…”
Section: The Pathophysiological State Of Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%
“…Moreover, the decrease of mitophagy can lead to excessive ROS in cardiac cells, further promote the release of cytochrome c and cysteine aspartate protease, disrupt the stability of mitochondria DNA, inhibit the activity of respiratory electron-transport chain, and reduce both oxygen utilization and consumption. It can even initiate mitochondrial apoptosis and induce mitochondrial damage (26, 88, [219][220][221][222][223][224]. Parkin overexpression increases mitophagy, which aggravates cell death through poisoning.…”
Section: Mitophagy and Poisoningmentioning
confidence: 99%